Integrated primary and behavioral health care in patient-centered medical homes for jail releasees with mental illness - Held, Mary Lehman (Criminal justice and behavior, 2012)
Many jail releasees have persistent physical and mental health needs that are frequently unaddressed, leading to high rearrest rates and return to jail. This article details the potential benefits and challenges of integrated health services during transition planning and return to the community and details lessons learned from a pilot program in Houston, Texas. It examines how patient-centered medical homes, a modality supported by policy changes at the federal level, provide one means of effective transition from jail to the community that integrates behavioral health services with primary care. Evidence from the pilot program suggests that effective integrated health services for jail releasees can help divert individuals from a cycle of recidivism.